(untitled) (Perner’s Contacts, 2020)
Strategic management is an essential part of the business management. It can also be a way to increase the competitiveness of enterprises. One of the possibilities of using strategic management tools in bus transport companies is just the concept of Balanced Scorecard (BSC) system. The BSC system consists of four perspectives - financial, customer, business and learning and growth perspective, which use a lot of indicators. When the enterprise is introducing the BSC system, it should be respected those perspectives. In fact, we analysed how companies in the Slovak Republic use BSC system in their own strategic management. The results of the survey is published in this paper. The aim of this article is to explain the methodology of the BSC system and benefits of implementing this system. It also determined the possibilities of using BSC system in practice, namely in bus transport companies.